2015
DOI: 10.1186/s12902-015-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D play a significant role in type 2 diabetes?

Abstract: BackgroundVitamin D deficiency reportedly is associated with type 2 diabetes (T2DM). We aim to examine whether 25-hydroxyvitamin D (25OHD) has clinically significant influence on hemoglobin glycation (HbA1c) and insulin resistance (HOMA-IR) in T2DM subjects.MethodsPresent study was carried out in 912 subjects (429 T2DM cases and 483 non-diabetic controls) from Western India. The enrolled study subjects were investigated for biochemical parameters like FBS, PPBS, HbA1c, FI, HOMA-IR and 25OHD levels in blood.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 34 publications
7
50
2
2
Order By: Relevance
“…In contrast, other studies, did not trace any difference in 25(OH)D between subjects with diabetes comparing to normal population. (32)(33)(34) Since the current study was conducted in Egypt, an area that receives adequate sunlight throughout the year, The high occurrence of vitamin D deficiency among participants encountered herein could be considered unexpected, and may be attributed to inadequate vitamin D intake which is prevalent around the world, regardless of the age or health status. Significantly lower levels of 25(OH) vitamin D3 in females than in males in diabetic subjects was found in this study.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, other studies, did not trace any difference in 25(OH)D between subjects with diabetes comparing to normal population. (32)(33)(34) Since the current study was conducted in Egypt, an area that receives adequate sunlight throughout the year, The high occurrence of vitamin D deficiency among participants encountered herein could be considered unexpected, and may be attributed to inadequate vitamin D intake which is prevalent around the world, regardless of the age or health status. Significantly lower levels of 25(OH) vitamin D3 in females than in males in diabetic subjects was found in this study.…”
Section: Discussionmentioning
confidence: 92%
“…The studies originated from 4 different continents. Of these, 11 studies were conducted in Asia, 6 studies were conducted in Europe, 1 study was conducted in North America, and 1 study was conducted in Oceania …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of data from observational studies (Table ), vitamin D deficiency was reported in healthy individuals and in individuals with T2DM . Vitamin D is correlated with markers of glucose metabolism in which higher serum 25(OH)D concentrations reflect lower levels of glucose, insulin, homeostatic model assessment–insulin resistance (HOMA‐IR), and particularly %HbA1c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that vitamin D may have extraskeletal effects, in addition to protecting against rickets and osteoporosis-related disorders, because vitamin D receptors are present in several different organs and tissues [1]. Several studies have shown an association between low levels of serum 25-hydroxyvitamin D [25(OH)D] and increased blood glucose, insulin resistance and incidence of Type 2 diabetes [2][3][4][5][6][7][8][9], whereas other studies have not [10][11][12][13]. Since the hypothesis that vitamin D may protect against cardiovascular disease was presented in 1981 [14], metaanalyses of cohort studies of general populations (containing people with and without diabetes) have shown that low baseline blood 25(OH)D predicts cardiovascular disease [15] and all-cause mortality [16,17].…”
Section: Introductionmentioning
confidence: 99%